TERJEMAHAN CONJUNCTIVE RELATION (CR) DALAM NOVEL MIXED BLESSINGS DAN NOVEL BERKAH PENUH COBAAN - Sriyono, Sriyono (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This paper discusses the form and meaning of conjunctive relation and how conjunctive relation is translated from source language into target language. The different system amongst languages in forming words, sentences or paragraph might represent peculiar form and meaning. As a part of element in determining logical meaning, conjunctive relation can be in the form of conjunction, verb, noun, preposition and implicit. Those forms signal how unity of a text is constructed. In translation, the use of conjunctive relation forms frequently make problem for translators since it is closely related to logical meaning in a text. In translating text, different meaning between two languages should be occasionally translated into different form and meaning of the two languages. To understand a text comprehensively, a reader must know the unity of a text. One of the aspects to determine unity of a text in translation is conjunctive relation. The unity of a text can be covered with the conjunctive relation which signal logical relation among clauses, sentences and paragraph, so that in translation cohesiveness of a text is interpreted well both in source text and target text.